Penahanan Tersangka/Terdakwa Pengguna Narkotika Oleh Aparat Penegak Hukum Dalam Perspektif Tujuan Penegakan Hukum - Syahrir Kuba (KRTHA BHAYANGKARA, 2023)
The phenomenon that occurs in Indonesia today is the increasingly widespread distribution of narcotics which causes the emergence of victims of narcotics abuse from a fairly large number of people, including students and undergratuade students as, then sentenced to imprisonment. Based on field observations, Investigators and Public Prosecutors still prioritize the provision as stated in Article 111 Section (1) and Article 112 Section (1), even though the facts show that to use Narcotics, a suspect / defendant is almost certain that they carry, buy or store and possess narcotics, then sentenced to imprisonment on the basis of Article 127 Section (1)a, Law Number 35 Year 2009, without considering Article 127 Section (3) which reads that the abuser must undergo medical rehabilitation and social rehabilitation, not prioritizing legal certainty. In 6 (six) judgement of the South Jakarta District Court, the Suspects or Defendants were all detained starting from the Investigation, Prosecution and judicial processes with a duration of detention between 104 days and 184 days, even though the actual proof was not too complicated because it started with a case of being caught red-handed until a sentence of imprisonment was sentenced by the South Jakarta District Court Judge.